2011
DOI: 10.1002/adsc.201100467
|View full text |Cite
|
Sign up to set email alerts
|

In situ Acidic Carbon Dioxide/Ethanol System for Selective Oxybromination of Aromatic Ethers Catalyzed by Copper Chloride

Abstract: An environmentally benign carbon dioxide/ethanol reversible acidic system was developed for the copper(II)‐catalyzed regioselective oxybromination of aromatic ethers without the need of any conventional acid additive and organic solvent. Good to excellent yields together with very good regioselectivity were achieved when easily available cupric chloride dihydrate was used as catalyst and lithium bromide as the cheap and easy‐to‐handle bromine source under supercritical carbon dioxide conditions. Notably, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…They also studied copper(II)-catalyzed regioselective oxybromination of aromatics in CO 2 /ethanol system. 187 Good to excellent yields as well as very good regioselectivity were achieved (CO 2 1 MPa, O 2 1 MPa, 100 C, 10 h). The authors believed that formation of ethylcarbonic acid was crucial for the promotion of the reaction.…”
Section: Comparison With Biphase Alcohol/ Co 2 System Alkylcarbonic Acidmentioning
confidence: 86%
“…They also studied copper(II)-catalyzed regioselective oxybromination of aromatics in CO 2 /ethanol system. 187 Good to excellent yields as well as very good regioselectivity were achieved (CO 2 1 MPa, O 2 1 MPa, 100 C, 10 h). The authors believed that formation of ethylcarbonic acid was crucial for the promotion of the reaction.…”
Section: Comparison With Biphase Alcohol/ Co 2 System Alkylcarbonic Acidmentioning
confidence: 86%
“…by SC-CO2 with ethanol as cosolvent (in variable proportions in the range 30 to 70%) at 80 °C and 25 MPa, concluding that ethanol increased in all the cases the oil recovery rate and Belayneh et al [29] pumped ethanol at concentrations of 2.5, 5 and 10% (mass rate of ethanol/mass rate of SC-CO2) into the extraction vessel, loaded with Camelina sativa seeds. These authors reported a significant increase in the extraction yield at all pressure and temperature levels (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) MPa; 50-70 °C, respectively). This increase in oil extraction yield is, in general, attributed to the increase in the polarity of the solvent mixture as a consequence of the addition of ethanol.…”
Section: Oil Extraction Yieldmentioning
confidence: 93%
“…All in all, this work, as a first step in a comprehensive valorization of rice bran using pressurized fluids, the study of the extraction of bioactive molecules and oil from rice bran using SC-CO2 and ethanol as cosolvent is carried out. The effect of the main process parameters temperature (40-60 °C), pressure (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and percentage of ethanol as cosolvent (from 0% (neat SC-CO2) to 10%) on the quality of the oil has been studied. The extracted oils have been completely characterized in terms of fatty acids profile and content in bioactive molecules such as polyphenols, flavonoids, oryzanols and tocopherols.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, CO 2 chemistry based on its capture and utilization deserves much attention and great efforts from the scientific community and industrial sectors. [2][3][4][5][6][7] On the other hand, CO 2 as an abundant and readily available C 1 resource has also shown significant potential and advantage in synthetic organic chemistry for production of value-added chemicals. [8][9][10][11][12] Besides profound achievements in chemical fixation of CO 2 , various feasible uses of CO 2 have been widely proposed, such as a sound reaction medium for green processes, 13 Lewis acid catalyst and/or promoter, 14 and tunable reagent for controlling chemical selectivity, 15 providing feature advantages from the viewpoint of green chemistry.…”
Section: Introductionmentioning
confidence: 99%